Biomaterial-Based Schwann Cell Transplantation and Schwann Cell-Derived Biomaterials for Nerve Regeneration - Rao, Zilong; Lin, Zudong; Song, Panpan; Quan, Daping; Bai, Ying (Frontiers in Cellular Neuroscience, 2022)
Schwann cells (SCs) dominate the regenerative behaviors after peripheral nerve injury by supporting axonal regrowth and remyelination. Previous reports also demonstrated that the existence of SCs is beneficial for nerve regeneration after traumatic injuries in central nervous system. Therefore, the transplantation of SCs/SC-like cells serves as a feasible cell therapy to reconstruct the microenvironment and promote nerve functional recovery for both peripheral and central nerve injury repair. However, direct cell transplantation often leads to low efficacy, due to injection induced cell damage and rapid loss in the circulatory system. In recent years, biomaterials have received great attention as functional carriers for effective cell transplantation. To better mimic the extracellular matrix (ECM), many biodegradable materials have been engineered with compositional and/or topological cues to maintain the biological properties of the SCs/SCs-like cells. In addition, ECM components or factors secreted by SCs also actively contribute to nerve regeneration. Such cell-free transplantation approaches may provide great promise in clinical translation. In this review, we first present the current bio-scaffolds engineered for SC transplantation and their achievement in animal models and clinical applications. To this end, we focus on the physical and biological properties of different biomaterials and highlight how these properties affect the biological behaviors of the SCs/SC-like cells. Second, the SC-derived biomaterials are also reviewed and discussed. Finally, the relationship between SCs and functional biomaterials is summarized, and the trends of their future development are predicted toward clinical applications.